Profil Kreativitas Siswa Reflektif dan Impulsif dalam Menyelesaikan Masalah Open-Ended - Setio Fuadi; Inggrit Diyah Ismaya; Eka Sulistiyaningsih; Puji Nugraheni (FKIP Universitas Mataram, 2026)
This study aims to describe the creativity profile of students with reflective and impulsive cognitive styles in solving open-ended mathematical problems involving fractions. This study is descriptive qualitative in nature. The subjects of this study were fifth-grade students at Surojoyo Public Elementary School who were selected through the Matching Familiar Figure Test (MFFT), consisting of two reflective students and two impulsive students. The subject selection technique was purposive sampling. The data collection techniques used open-ended problem tests and in-depth interviews. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that reflective students optimally fulfilled the four indicators of creativity, namely fluency, flexibility, originality, and elaboration. Reflective students were able to produce various alternative answers, use diverse strategies, and explain the steps to the solution in detail. In contrast, impulsive students only showed good ability in the fluency indicator, but were still limited in flexibility and originality. Impulsive students tended to use simple and homogeneous solution strategies to obtain answers quickly